Simulation to improve CO2 capture using vapor recompression combined with split stream process: article / Muhammad Hafeez Azhar, Prof. Madya Dr. Ruzitah Mohd Salleh - Azhar, Muhammad Hafeez; Mohd Salleh, Ruzitah (2017)
In this era of globalization, carbon dioxide (CO2) has become one of the main component of greenhouse gases emitted into the atmosphere. Large quantities of CO2 is released through power generation from fossil fuel-fired power plants. Due to this problem, CO2 capture technologies have been developed which it is one of the techniques that could be used to reduce CO2 emissions from human activities. The most well-known technology for post combustion CO2 capture from exhaust gas is absorption in amine-based solvent followed by desorption. The solvent used in this absorption process is monoethanolamine (MEA). However, this method encountered drawback such as low performance of CO2 capture efficiency. The objective of this study is to improve CO2 capture using vapor recompression combined with split-stream process and study the parameters that affect CO2 capture. Simulation using Aspen HYSYS version 8.8 was used in this study. The fluid package used was Amine Property Package (acid gas). The inlet temperature and pressure at the absorber and concentration of MEA were varied to investigate the effect on CO2 capture. The result shows that the CO2 removal efficiency increases as the inlet temperature and concentration of MEA increases. However, the increment was small which only gave small effect on percentage of CO2 removal. In contrast with inlet pressure at the absorber, CO2 removal efficiency was highly dependent on the pressure and gave high impact on percentage of CO2 removal. The best operating condition obtained from this study was at 80 oC, 400 kpa and 0.14 wt% MEA concentration.